2016
DOI: 10.1111/cmi.12569
|View full text |Cite
|
Sign up to set email alerts
|

The novel chlamydial adhesin CPn0473 mediates the lipid raft‐dependent uptake ofChlamydia pneumoniae

Abstract: Summary Chlamydiae are Gram‐negative, obligate intracellular pathogens that pose a serious threat to public health worldwide. Chlamydial surface molecules are essential for host cell invasion. The first interaction with the host cell is thereby accomplished by the Outer membrane complex protein B (OmcB) binding to heparan sulfate moieties on the host cell surface, followed by the interaction of the chlamydial polymorphic membrane proteins (Pmps) with host cell receptors. Specifically, the interaction of the Pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…In addition, entry via cholesterol‐rich lipid rafts has also been described for Chlamydia spp. (Fechtner, Galle, & Hegemann, ; Norkin, Wolfrom, & Stuart, ). Uptake requires the delivery of bacterial proteins into the host cell cytosol using a type III secretion system (Hsia, Pannekoek, Ingerowski, & Bavoil, ; Hybiske & Stephens, ; Nans, Ford, & Hayward, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, entry via cholesterol‐rich lipid rafts has also been described for Chlamydia spp. (Fechtner, Galle, & Hegemann, ; Norkin, Wolfrom, & Stuart, ). Uptake requires the delivery of bacterial proteins into the host cell cytosol using a type III secretion system (Hsia, Pannekoek, Ingerowski, & Bavoil, ; Hybiske & Stephens, ; Nans, Ford, & Hayward, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, disruption of lipid rafts by pretreating the AEC with Filipin significantly reduced the numbers of intracellular bacteria suggesting a role for lipid raft targeting and aggregation in M. tb internalization by type 2 AEC. Whether it is M. tb adhesin:lipid raft interactions that promote uptake by AEC (or other non-phagocytic cells), either directly or through co-localized receptors, remains to be investigated; however, adhesins of other bacterial pathogens have been shown to mediate their uptake by non-phagocytic cells through lipid raft-dependent mechanisms including Chlamydia pneumoniae (Fechtner et al, 2016), Streptococcus pneumonia (Yamaguchi et al, 2013), and Shiga-toxigenic E. coli (Rogers et al, 2012).…”
Section: Potential Mechanisms For M Tb Uptake By Aecmentioning
confidence: 99%
“…In order to test whether the proteins have adhesive capacities, we performed adhesion studies in which human HEp-2 cells are tested for binding of selected recombinant (r) cluster proteins ( Figure 7A). Interestingly, compared to the controls, the chlamydial adhesin rCPn0473 (Fechtner et al, 2016) and rGST, we observed that only rMbp1 and rMbp4 proteins carrying a DUF575 domain were able to adhere to the human cells, while those carrying only the DUF562 (rMbp3) or no DUF at all (rMbp2) did not bind to the cells (Figure 7A). Furthermore, we could show that the DUF575 domain is essential for adhesion, as rMbp4 121−672 , a DUF575 deletion variant, clearly showed strongly reduced adhesion to HEp-2 ( Figure 7A).…”
Section: Proteins Of the Cluster Can Bind To Membranes But Are No Adhmentioning
confidence: 88%
“…Initial contact between the Cpn EB and the host cell is mediated by binding of conserved adhesins to various host cell structures. Of these, OmcB binds to heparansulfate-like proteoglycans (GAG), while LipP (CPn0473) binds to phospholipids in the host membrane, and Pmp21 interacts with the epidermal growth factor receptor (EGFR), serving as both an adhesin and an invasin (Moelleken and Hegemann, 2008;Mölleken et al, 2013;Fechtner et al, 2016). This last interaction promotes internalization of the EB by activating the EGFR, and the developing inclusion at first remains associated with the activated receptor (Mölleken et al, 2013).…”
Section: Introductionmentioning
confidence: 99%